2018
DOI: 10.3390/ncrna4030022
|View full text |Cite
|
Sign up to set email alerts
|

Novel Roles of Non-Coding RNAs in Opioid Signaling and Cardioprotection

Abstract: Cardiovascular disease (CVD) is a significant cause of morbidity and mortality across the world. A large proportion of CVD deaths are secondary to coronary artery disease (CAD) and myocardial infarction (MI). Even though prevention is the best strategy to reduce risk factors associated with MI, the use of cardioprotective interventions aimed at improving patient outcomes is of great interest. Opioid conditioning has been shown to be effective in reducing myocardial ischemia-reperfusion injury (IRI) and cardiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 179 publications
0
17
0
Order By: Relevance
“…Studies have looked at the cardiotoxicity of methadone, and after finding some significant results, they recommended a review of the prescription guideline of methadone among patients with cardiovascular compromise [17,19]. Other studies similar to the current study have also submitted that both short-term and long-term opioid use did not significantly increase the risk of heart disease [5,20]. When reviewing the current literature, some studies suggested that long-term opioid medication may have very little direct effects on the functions of the heart.…”
Section: Discussionmentioning
confidence: 77%
“…Studies have looked at the cardiotoxicity of methadone, and after finding some significant results, they recommended a review of the prescription guideline of methadone among patients with cardiovascular compromise [17,19]. Other studies similar to the current study have also submitted that both short-term and long-term opioid use did not significantly increase the risk of heart disease [5,20]. When reviewing the current literature, some studies suggested that long-term opioid medication may have very little direct effects on the functions of the heart.…”
Section: Discussionmentioning
confidence: 77%
“…Although a large number of novel biomarkers, such as genetic variation, 34 micro-ribonucleic acid (RNA) 35 and LncRNA, 36 have emerged in recent years, their predictive performances on the outcomes of CAD patients after PCI are limited and performing detection methods for these biomarkers is expensive. Recently, the prognostic role of haematologic biomarkers in patients with cardiovascular disease has been recognized, such as the monocyte-to-HDL-C ratio, 37 MPV, 21,22 RDW, 23 GGT [15][16][17][18][19] and platelet count, 20 which are efficient biomarkers for predicting outcomes in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids participate in a reduction of damage to myocardial intracellular structures, a decrease in the dysfunction of the cardiac contractile machinery, and a direct reduction in arrhythmias [104]. Opioids activate the δ and k receptors coupled to the G i proteins and also can activate the µ receptors, but this has very low expression in cardiomyocytes [105]. The δ receptor is most important in the preconditioning phenomena, and this defense can be abolished using the pharmacological antagonist naloxone [104,106].…”
Section: Extra-renal Opioid Preconditioning Mechanismsmentioning
confidence: 99%
“…Morphine or remifentanil administration before myocardial IRI can induce cardioprotection through the µ receptors via the ERK/GSK-3b signaling pathway [109]. This receptor has also been postulated as a potential therapeutic target for opioid-induced protection during heart failure [105,109].…”
Section: Extra-renal Opioid Preconditioning Mechanismsmentioning
confidence: 99%